Esophageal Rhabdoid-Like Tumor: A Rare Disease With Aggressive Clinical Behavior - Lovece, Andrea; Bernardi, Daniele; Bruni, Barbara; Asti, Emanuele; Clemente, Claudio; Bonavina, Luigi (Frontiers in Surgery, 2020)
Background: Malignant rhabdoid tumor is a kidney childhood tumor with aggressive clinical behavior and a wide spectrum of histologic, immunophenotypic, and cytogenetic findings. Extra-renal rhabdoid tumors have been reported in the brain, breast, liver, pancreas, bladder, vulva, prostate, and colon. To date, only nine cases of esophageal rhabdoid tumors have been described, all in patients over 50-year old. We add to the current literature the case of an esophageal, poorly differentiated rhabdoid tumor occurring in a young man. Case Report: A 24-year-old man was referred for progressive dysphagia, retrosternal pain, nausea, and food regurgitation. Esophagogastroduodenoscopy showed an obstructing neoplastic lesion of the distal esophagus associated with Barrett's esophagus. Biopsies revealed undifferentiated esophageal cancer with epithelial morphology and immunohistochemistry positive for CK pan, CK 7 e CK 8-18. Minimally invasive esophagectomy and extended lymphadenectomy was performed. Histopathology showed a poorly differentiated tumor, with morphologic characteristics of rhabdoid tumor, central necrosis and transmural infiltration of the esophageal wall. Definitive immunohistochemistry was positive for vimentin, CD34, synaptophysin, and INI1. Conclusion: Esophageal rhabdoid tumor is extremely rare and highly aggressive, with only few patients alive at 1 year follow-up, according to our review. Immunohistochemistry characterization is critical for diagnosis. Minimally invasive esophagectomy is an appealing and possibly less morbid option compared to open surgery. However, further research is needed to investigate the potential role of targeted immunotherapy.